Raising Awareness to Prevent Sexual Violence for Mosque Teenager - Rosmalinda, Rosmalinda; Siregar, Ade Rahmawati; Arifiyanto, Joiverdia; Agusmidah, Agusmidah; Siagian, Fahrizal S. (Kosmik Hukum, 2025)
This article was conducted in the form of community service “training of trainer”. The goal of this activity is to improve youth knowledge, understanding, skills and roles in preventing sexual violence. This research involves the committee and members of mosque youth who trained in preventing sexual violence. Adult education methods are used in community service as well as legal research to analyze participation of mosque youth in preventing sexual violence at worship place use a legal, case and conceptual approach. The research found: (1) The number of sexual violence cases increases every year in susceptible locations such as public spaces, terminals/stations, roadsides/sidewalks, public transportation, mass or social media, residential areas, workplaces/offices and campuses. (2) The absence of worship place on susceptible locations list does not mean sexual harassment against women and children has not existed. It could be happened to anyone regardless of gender, age, religion or social background. (3) knowledge, understanding, ability and role to prevent sexual violence among mosque youth increased after participated and practice through "Let's Practice Being a Trainer/Facilitator on Sexual Violence Prevention ". As conclusions: (1) mosque youth have an important role to reduce the number of various forms of and/or prevent of sexual violence, (2) the Indonesian Mosque Youth Communication Agency (BKPRMI) has capacity and roles to improve the knowledge, ability and role of mosque youth in preventing sexual violence, especially in the mosque/prayer room area.